2012
DOI: 10.1249/jsr.0b013e3182699489
|View full text |Cite
|
Sign up to set email alerts
|

Injuries and Medical Issues in Softball

Abstract: Softball is enjoyed by millions of female and male athletes of all ages and competitive levels. Windmill pitchers are at risk for developing overuse injuries in the throwing arm. Improper mechanics and lack of pitch counts may increase the risk for developing a pitching-related injury. Softball-related overuse injuries include proximal biceps tendinitis, upper extremity stress fractures, and ulnar neuritis. Acute injuries commonly occur in the lower extremity and include both fractures and ligamentous injuries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
0
18
1
Order By: Relevance
“…In terms of TL injuries, the highest proportion was to the head/face (40.8%). Although we tended to report higher proportions of injuries to the upper extremities and head/face, other researchers 12,13 reported higher proportions of injuries (40% to 43%) to the lower extremities. When we consider only TL injuries, our findings suggest that a smaller proportion of injuries were to the lower extremities than previously described.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…In terms of TL injuries, the highest proportion was to the head/face (40.8%). Although we tended to report higher proportions of injuries to the upper extremities and head/face, other researchers 12,13 reported higher proportions of injuries (40% to 43%) to the lower extremities. When we consider only TL injuries, our findings suggest that a smaller proportion of injuries were to the lower extremities than previously described.…”
Section: Discussioncontrasting
confidence: 72%
“…The shoulder was the most frequently injured body part in several softball studies. 2,12,13 Further, of all the NTL injuries in our study, the highest proportions were to the shoulder (15.1%) and hand/fingers (12.3%). In terms of TL injuries, the highest proportion was to the head/face (40.8%).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The "acceleration phase" occurs from the top of the backswing (arm directly overhead) to ball release [2,5,46,47]. Data supporting both mechanical [2,27,46,47] and injury components [3,6,40,41] of softball pitching have been published, however there have yet to be data describing the pitching mechanics of those experiencing upper extremity pain.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that both participation [13] and injury rates in fast-pitch softball are comparable to those reported in the baseball population [19,[32][33][34][35]40]. When injuries in fast-pitch softball were examined, the major focus has been on overuse [4,6,14,19,20,24,26,39,40,43]. Approximately 370 overuse injuries were reported in collegiate and high school fast-pitch softball players from 2004-2009 [37].…”
Section: Introductionmentioning
confidence: 99%